Pengaruh Tata Kelola Perusahaan Terhadap Profitabilitas Perusahaan di Sektor Perbankan - Natanael Albert Frumentius; Yulius Jogi Christiawan (Business Accounting Review, 2020)
This study aimed to examine the direct affect of board size, board meeting, board independent, firm size, and leverage on the profitability in Indonesia banking companies. The sample used in the study consisted of 44 banking companies listed on Indonesia Stock Exchange (IDX) with observation years during 2014-2018. Data processing using Gretl software.The results found board size had significant negative affect on profitability. Board meeting had significant affect on profitability. Board independent had no significant affect on profitability. Firm size had significant positive affect on profitability. Leverage had significant negative affect on profitability.